(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Objective: To assess the correlation of birth weight with other anthropometric variables and their appropriateness in prediction and detection of low birth weight babies. Methodology: It was a hospital-based cross-sectional observational study, conducted over 100 newborn babies within 24 hours of their birth. Birth weight and other anthropometric variables were recorded and analyzed with statistical package for social science (SPSS-17) and Students t-test, Chi-squared (?2), ANOVA and Pearson correlation tests were done to test the hypothesis and level of significance was set as p <0.05. Result: All the anthropometric variables were well correlated with birth-weight, irrespective of gestational age (p<0.01). The highest correlation was found with chest circumference (r = 0.962), while the lowest correlation was observed with calf circumference (r 0.923). Conclusion: All anthropometric variables except calf circumference can be considered as appropriate indicators for identifying neonates require special attention and intervention for low birth weight (LBW) where weighing machine or facilities for ultrasonography is not readily available. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12189 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 29-32